Bipolar Log-Intensity-Variance Histogram Method for Local Image Patch Intensity Change Measurements. (2nd June 2019) - Wang, Han; Shi, Quan; Xu, Zhihuo; Wei, Ming; Ko, Hanseok
Abstract : For a fixed-position camera, the intensity changes of an image pixel are often caused by object movement or illumination change. This paper focuses on such a problem: given two adjacent local image patches, how can the causes of intensity change be determined? A bipolar log-intensity-variance histogram is proposed to describe the intensity variations on the chaos phase plot subspace. This is combined with two sigmoid functions to construct a probabilistic measure function. Experimental results show that the proposed measurements are more effective and robust than conventional methods to the cause of variation in image intensity.